UNDERSTANDING HALAL FOOD CONSUMER DECISION-MAKING: THE INTEGRATION OF KNOWLEDGE INTO THE THEORY OF PLANNED BEHAVIOR - Harwati Harwati (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2026)
The Theory of Planned Behavior (TPB) provides a robust conceptual framework for comprehending and forecasting consumer behavior, specifically regarding an individual's inclination to consume halal food. The purpose of this study is to investigate the extent of TPB to which knowledge affects attitude, subjective norms, and consumer behavior in consuming halal products. This study was conducted using a partial-least-squares structural-equation-modeling (PLS-SEM) technique to test and estimate relationships between variables in the case context. Using primary data collection method, 1200 questionnaires were distributed to muslim consumers in Yogyakarta, Indonesia. The responses collected were 1181 completed questionnaires representing 98 percent response rate. Goodness of fit for the structural model shows requirement in terms of Chi-Square: 1127.633; P-Value: 000; GFI: 0.911; and RMSEA; 0.048. This study provides on the significant impact of knowledge on consumer decision-making regarding the consumption of halal products. The result of this study also reveals the complex mechanisms by which knowledge influences attitudes, subjective norms, perceived behavioural control, and finally, purchasing behaviour.